Microwave-activated Synthetic Route to Various Biologically Important Heterocycles Involving Transition Metal Catalysts - Basu, Soumyadip; Mukhopadhyay, Chhanda (Current Microwave Chemistry, 2023)
This study incorporates the assembly of development methodologies of microwave-activated protocol involving transition metal catalysts for the synthesis of numerous biologically important heterocycles during the past few years. Herein, it highlights the potential of transition metal salts as catalysts in multicomponent reactions performed under microwave conditions for the formation of oxygen, nitrogen, and sulphur-containing bioactive heterocycle moieties. Microwaveactivated organic synthesis has been well-utilized as an alternative to conventional methodology in pharmaceutical companies due to its potential to significantly improve the rate and consequently diminish the time span of the synthetic process. The traditional methods involving transition metal catalysts for synthesizing bioactive heterocyclic molecules are prolonged and, thus, difficult to meet the requirements for the timely supply of these important compounds. In our review, our main focus is on integrating such synthetic strategies involving transition metal catalysis with a microwaveactivated multicomponent approach for developing bioactive heterocycles.
Keywords: transition metal salt catalyst